Decision Support System for Determining Textile Industry Waste Water Treatment Institution in Web Based Citarum River - Febriyanti, Siska; Rumanti, Augustina Asih; Supratman, Nurdinintya Athari (Metris: Jurnal Sains dan Teknologi, 2019)
The Citarum River is the longest river in West Java. The river participates in the development of the Indonesian economy by 20% of GDP (Gross Domestic Product). In 2018, the citarum river ecosystem structuring survey team found 31 factories in the Bandung Regency region that dumped the waste produced directly into the Citarum River, one of which was the textile industry. In the production process the textile industry uses textile dyes containing azo dyes. The compound has the potential to produce aminobenzen or aniline which causes pollution. The lack of a communal Waste Water Treatment Plant (IPAL) and improper location is a factor that causes the industry to dispose of production waste water directly into the Citarum River. This study aims to support government activities in improving the Citarum River by designing a Decision Support System (DSS) using a website-based Analytical Hierarchy Process (AHP) method to determine the right location to build a communal WWTP. .